Personal innovativeness based self-esteem: establishing construct and predictive validity - Mahmood, Anwar (2022)
The most crucial element of new construct development process is the external phase that needs to be executed in order to achieve a fully functional psychological construct. The external phase of new construct development includes development of nomological network to demonstrate construct’s theoretical validity, predictive validity, or other criterion-related validities. To achieve this objective, this research, therefore, aims to validate a newly proposed innovativeness based psychological construct titled “innovativeness based self-esteem” (IBSE) which is confined within self-concept paradigm. To validate this construct, a three-step approach has been devised. First, the study developed a nomological network resulting in a set of hypotheses directing efforts to validate the construct empirically in organizational settings. Second, the theory of interactionism was tested for innovativeness based self-esteem (IBSE). Third, the test of predictive validity for innovativeness based selfesteem (IBSE) was conducted. Survey research design was adopted for this study due to its versatility because scholars argued that survey design is typically most suitable design, therefore, widely adopted by construct validation studies. To validate innovativeness based self-esteem construct, standard self-rated and supervisor-rated online questionnaires were administered to 150 permanent employees (technologists, engineers, researchers) and their supervisors working in Research and Development (R&D) departments of Science and Technology (S&T) organizations of Pakistan at Time 1. A second sample was taken from same employees at Time 2 i.e., after 3 months. The second sample was only required to establish an evidence of test-retest reliability of innovativeness based self-esteem (IBSE). The study tested the hypotheses by applying Pearson product moment correlations, hierarchical linear regression, and Preacher and Hayes moderation analysis. Overall study results proved that innovativeness based self-esteem (IBSE) is a theoretically valid construct and stable over time. At last, all the results were discussed in the light of underpinned theories and reviewed literature along with proper justifications. No doubt, theorizing the innovativeness based self-esteem (IBSE) not only offers implications for self-concept theory, self-esteem theory, and personal innovativeness theory but also recommends that managers should consider extent of innovativeness based self-esteem (IBSE) of their workforce, along with other dispositional factors, in order to achieve desired innovative job performance outcomes.